Recent Advances in Nano Patterning and Nano Imprint Lithography for Biological Applications - N., Vigneswaran; Fahmi, Samsuri; Balu, Ranganathan; Padmapriya (Elsevier Ltd, 2014)
Nano patterning and Nanoimprint lithography [NIL] has advanced to great heights in recent years. Customizing the surface at micro and nano scale is of great demand. It facilitates the handling and working at micro and nano scale level. Its applications towards medical field are growing day by day. Precise surface patterning with nanometer resolution has great potential in many medical and biological applications. It also provides a platform for fundamental studies of molecular and cell biology. This review article comprises of current trends and future scope of nano patterning and NIL. In this article we particularly focus on biological applications.